The The Male Teachers’ Perceptions on Early Childhood Children’s Education about Wellbeing - Seno, Seno; Utanto, Yuli; Sugiyo Pranoto, Yuli Kurniawati (Journal of Primary Education, 2021)
The wellbeing of formal early childhood education teachers in Indonesia has been improving since the government issued a teacher certification program. The qualified teachers with an undergraduate degree of education could join the certification program for teachers. This research aims to reveal the meaning of wellbeing for male teachers of early childhood education. It applied survey and interview methods. The subjects consisted of 16 male teachers of early childhood education in Boyolali. The data were collected with Google Form. Then, it was continued by interviewing three male teachers. The data analysis was descriptive qualitative. The findings were the teaching experience for each different subject. The meaning of teaching is to motivate and to encourage the understanding of the teaching concept as a good deed. In this research, it referred to how the subjects perceived life as teachers and made it an everlasting deed to create a better generation for the country. There were 11 respondents who stated that being early childhood education teachers made them having well-being. Being early childhood education for the male teachers meant to have passion, values, and ideals. It could provide them various experiences such as being patient, providing excellent models as if they were the learners' parents, working while worshiping, contributing in the parenting field, and developing early childhood education